Informational environments and the relative information content of analyst recommendations and insider trades - Wang, Sean (Accounting, Organizations and Society, 2019)
Analysts and insiders increase price informativeness by revealing new information to financial markets, and prior work has shown that these parties hold both firm-specific and aggregate information. This study examines how the level of informational efficiency with respect to a stock price's firm and industry-level information environment can differently mediate the information content of analyst recommendations and insider trades. I find that (1) the decrease in information revealed by insider trades is larger than that from analyst recommendations when a stock's price is more efficient with respect to firm-specific information, while (2) the increase in information revealed by analyst recommendations is larger than that from insider trades when a stock's price is less efficient with respect to industry-level information. Taken together, my results indicate that analysts (insiders) may have relative informational expertise with regards to industry (firm) information, and that both appear to rely on their specific expertise when informing prices.